Optimizing the Synthesis of Novel Calcium Carbonate/Cobalt Oxide Nanocomposite With Highest Antifungal Activity - Nima Fallahnia; Mohammad Salmani Mobarakeh; Hasti Sarabikia; Mohsen Safaei (Advances in Materials Science and Engineering)
Today, the rise of opportunistic infections and their resistance to current antifungal drugs has led to the inevitable need to produce effective antimicrobials at a reasonable cost. This study aimed at producing a calcium carbonate/cobalt oxide nanocomposite with the most excellent antifungal activity against Candida albicans (C. albicans). Thus, nine experimental designs using the Taguchi technique were utilized to discover the greatest combination of parameters for antifungal activity. The colony-forming unit (CFU) method was used to test the produced nanocomposites’ antifungal properties against C. albicans. The results indicated that the synthesized nanocomposite in optimal conditions (20 mg/mL of calcium carbonate, 3 mg/mL of cobalt oxide, and 90 min of stirring time) could inhibit the growth of C. albicans by more than 74%. Various analyses were applied to determine the structural properties of the calcium carbonate/cobalt oxide nanocomposite, and its constituents revealed the fabricated nanocomposite’s desirable properties. In the study, the nanocomposite was an efficient antifungal agent that might be employed in various fields, including medicine, dentistry, and life sciences.